Differences in Preseason Aerobic Fitness Screening in Professional and Pre-Professional Modern Dancers. Issue 1 (March 2016) - Bronner, Shaw; Codman, Emma; Hash-Campbell, Dana; Ojofeitimi, Sheyi
The aerobic demands of today's dance repertoire warrant understanding of the current cardiorespiratory fitness of dancers. The purpose of this study was to compare aerobic fitness levels of professional and pre-professional modern dancers and determine change over time. A retrospective analysis of four groups, two professional, and two pre-professional, was conducted in preseason annual screens, occurring before the professional dancers' rehearsal period and the students' academic training. Resting (HRrest ), peak (HRpeak ), and recovery (HRrecov ) heart rate, and blood pressure (BP) were compared in 577 dancers, using an accelerated 3-minute step test. Smoking, asthma, and aerobic and cross training rates between groups were also compared. A 4 (group) X 2 (gender) MANOVA design determined differences between groups and genders in all dependent variables (p < 0.05). Using a repeated measures ANOVA design, we compared a subgroup over 3 years and one pre-professional group over 4 years. There were differences between groups in systolic BP and all HR variables (p < 0.001). Professional dancers reflected better cardiorespiratory fitness than pre-professional dancers. There were differences between groups in aerobic and cross training activities but no differences in smoking incidence or asthma rates. Pre-professional dancers demonstrated improvement in aerobic fitness over time (p = 0.006) while professionals did not change. Professional dancers display better aerobic fitness, which may reflect their performance demands. Wellness programs appear to enhance fitness in pre-professional dance students over time. Additional aerobic training is recommended for preprofessional modern dance students to prepare them for the performance demands of a professional career.